The Role of Employee Engagement in Enhancing Organizational Performance: A Comprehensive Study in Health Care Centers Chennai - Vetrivel, V.; Christopher David, M. Prabhakar; Deepa, S.; Gokulakrishnan, A. (Journal of Neonatal Surgery, 2025)
Employee engagement plays a pivotal role in determining organizational performance, particularly in healthcare settings where the quality of care and operational efficiency are crucial. This study examines the factors influencing employee engagement and their impact on organizational performance in healthcare centers in Chennai. A sample of 270 healthcare employees participated in a structured survey, which measured variables such as leadership style, workplace environment, recognition systems, career development, and work-life balance. Descriptive statistics were employed to summarize the data, revealing a diverse sample with varying perceptions of engagement-related factors. Correlation analysis demonstrated that work-life balance had the strongest positive relationship with employee engagement, followed by workplace environment and recognition systems. Multiple regression analysis, however, indicated that none of the independent variables showed a statistically significant impact on employee engagement when controlling for other factors, suggesting that engagement is influenced by more complex and unmeasured dynamics. The study highlights the importance of promoting a healthy work-life balance and creating a positive work environment to enhance employee engagement in healthcare settings. However, it also suggests that further research is needed to explore additional variables that might influence engagement and performance. The findings provide practical implications for healthcare administrators looking to improve employee engagement and, by extension, organizational performance. A more comprehensive understanding of employee engagement will help develop strategies that increase productivity, reduce turnover, and enhance patient care quality in healthcare centers